Association of metabolic syndrome with carotid atherosclerosis in low-income Chinese individuals: A population-based study - Zhan, Changqing; Wang, Qiao; Chen, Zongsheng; Pang, Hongbo; Tu, Jun; Ning, Xianjia; Wang, Jinghua; Fei, Shizao; Ji, Xuelei (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to explore the association of the presence and number of components of metabolic syndrome (MetS) with carotid atherosclerosis by measuring the presence of carotid plaque and total plaque area (TPA) in a population from a low-income area with high incidence of stroke of northern China. Methods: A cross-sectional study was conducted in a rural area of Tianjin, China from April 2014 to January 2015. The presence of plaque and TPA measurement was determined by carotid ultrasound. The presence and number of components of MetS was ascertained using the modified International Diabetes Federation criteria for the Asian population. Results: Among a total of 3583 individuals aged ≥ 45 years, the overall prevalence of MetS was 54.5%. MetS and its components were related to the presence of carotid plaque as well as TPA. Multivariate analysis showed MetS was associated with a 20% higher risk of carotid plaque presence (95% confidence interval: 1.01, 1.42; P = 0.036) and an 18% increase in TPA (95% confidence interval: 0.08, 0.27; P < 0.001). The number of MetS components showed an increasing trend with the risk of carotid plaque presence and increased TPA. Among single components of MetS, high BP accounted for the largest proportion and was an independent risk factor of carotid plaque and increased TPA. Conclusions: Among individuals aged 45 years or more, we confirmed MetS and its components were associated with carotid atherosclerosis in a low-income population of northern China. The presence of MetS and a higher number of MetS components exacerbated the risk of carotid atherosclerosis; among the five MetS components, high blood pressure was associated with the greatest risk. Targeted atherosclerosis prevention and intervention should include identification and treatment of MetS, especially high blood pressure.